USE OF CLUSTER SYSTEM IN INCREASE OF EXPORT CAPACITY IN TEXTILE INDUSTRY - Solijonov Shoxruxbek Alisher o‘g‘li (European Science Publishing, 2024)
In this scientific article, ways to increase the economic efficiency of the use of the cluster system in increasing the export potential of the textile industry in Uzbekistan and the actual problems in the development of the textile industry have been determined, and proposals and recommendations have been developed for their elimination.
Keywords: textile industry, export, import, cluster system, production, lean production, localization of production, re-production, management efficiency, competitive market, management mechanism.